Biodegradation, ecotoxicity and UV254/H2O2 treatment of imidazole, 1-methyl-imidazole and N, N'-alkyl-imidazolium chlorides in water. (1st December 2016) - Spasiano, D.; Siciliano, A.; Race, M.; Marotta, R.; Guida, M.; Andreozzi, R.; Pirozzi, F.
Abstract: Imidazole-based compounds are used as reagents for the manufacturing of other compounds including imidazolium-based ionic liquids, which have been recently proposed as a green alternative to conventional solvents. Since some imidazole-based compounds have been demonstrated to be harmful to aquatic organisms, the removal of imidazole, 1-methylimidazole, 1-ethyl-3-methyl-imidazolium chloride and 1-butyl-3-methyl-imidazolium chloride from aqueous solutions was attempted by biological oxidation, direct UV254 photolysis, and UV254 /H2 O2 process at pH 5.5 and 8.5. Results showed that UV254 /H2 O2 treatment is an effective tool for the removal of the selected compounds at both pHs. In fact, the kinetic constants of the reaction between the photogenerated HO radicals and the four target compounds, estimated by means of both numerical and competition kinetic method, range between 2.32·10 9 M −1 s −1 and 5.52 ·10 9 M −1 s −1 . Moreover, an ecotoxicity assessment of the contaminated water before and after initial treatment without further processing was assessed by using two living aquatic organisms: Raphidocelis subcapitata and Daphnia magna . The results of this assessment not only corresponded closely to previous findings (in terms of EC50 values) reported in the literature, but also indicated that, in some cases, UV254 /H2 O2 oxidation by-products could be even more toxic than parent compounds. Graphical abstract: Highlights: UV/H2 O2 process was used to remove imidazole-based compounds in aqueous solutions. The kinetic constants for HO attack on imidazole and its derivatives were estimated. The ecotoxicity evolution was monitored during the chemical process. An ecotoxicity increase was observed during the treatment of alkylimidazolium salts.